1993
DOI: 10.1002/hipo.450030213
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of glutamate is regulated by calcium and protein kinase C in rat hippocampal slices exposed to ischemic states

Abstract: There is now convincing evidence that excessive accumulation of the excitatory amino acid glutamate (Glu) in the extracellular space is toxic to neurons. However, the regulation of the release and uptake of Glu in producing this toxic concentration has not been adequately ascertained. The authors report that in hippocampal slices, the output of Glu significantly increased under in vitro ischemic states. Glu in the extracellular space increased fivefold. Since daurisoline, a drug that blocks N-type Ca2+ channel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…In addition, some of the toxic effects of NO may be linked to the activity of PKC (Maiese et al, 1993b,c). PKC ac tivity can regulate the release of glutamate (Lu et al, 1993) during ischemia, and down-regulation of PKC activity has been shown to protect neurons Vol. 15, No.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, some of the toxic effects of NO may be linked to the activity of PKC (Maiese et al, 1993b,c). PKC ac tivity can regulate the release of glutamate (Lu et al, 1993) during ischemia, and down-regulation of PKC activity has been shown to protect neurons Vol. 15, No.…”
Section: Discussionmentioning
confidence: 99%
“…For example, protein kinase C (PKC) can alter the toxic effects of both anoxia and NO. During cerebral ischemia, increased levels of PKC are present in the hippocampal CAl region (Cardell et al, 1990;Hara et al, 1990) and PKC activity can regulate the release of glu tamate (Lu et al, 1993), suggesting that PKC activation may lead to ischemic neuronal dam age. During periods of global ischemia, agents that decrease PKC activity can prevent neuronal damage (Hara et al, 1990).…”
mentioning
confidence: 99%
“…Glutamate, the excitatory neurotransmitter in the retina, is released by photoreceptors, bipolar cells and ganglion cells and mediates the transfer of visual signals from the retina to the brain (Massey 1990). However, augmented release of glutamate and its accumulation in extracellular spaces in hypoxic-ischemic conditions leading to activation of glutamate receptors has been implicated in hypoxic/ischemic neuronal death (Benveniste et al 1984; Lu et al 1993). Glutamate neurotoxicity is considered as the underlying problem in retinal neuropathies and neurodegenerative conditions such as glaucoma (Dreyer 1998).…”
Section: Hypoxia-ischemia and Excitotoxicitymentioning
confidence: 99%
“…The discovery of glutamate as an excitotoxin in the central nervous system has contributed to the understanding of the molecular mechanisms underlying the pathogenesis of ischaemic neuron damage (Meldrum, 1985;Rothman and Olney, 1986;Lu et al, 1991aLu et al, , 1993. It is known that brain regions enriched in glutamate receptors, including the hippocampus, are particularly vulnerable to ischaemic neuronal damage (Jorgenson e t a l .…”
Section: Introductionmentioning
confidence: 97%